Rancang Bangun Alat Ukur Tingkat Manis Buah Jeruk Menggunakan Sensor Kapasitor Semi Silinder Berbasis Arduino - Grace Pricilya Michiko; Arif Surtono; Humairoh Ratu Ayu; Junaidi Junaidi (Jurnal Teori dan Aplikasi Fisika, 2024)
Abstract. It has been realized the design of the orange based sweet level measuring device using an arduino based semi cylinder capacitor sensor. This study was conducted by providing input to the capacitor plates using an oscillator with a variety of frequency values of 10 KHz, 100 KHz, and 1 MHz. The oscillator used is the IC XR-2206 type. The sweet level of orange fruit is measured using a pocket refractometer otago pal-?. Semi cylinder capacitor sensor testing is carried out on 16 oranges. The most optimal measurement results are obtained in a 100 KHz frequency variation because the graph of the measurement results drops linearly. The voltage range at a frequency of 100 KHz is 200 - 2000 mV, with a brix value obtained between 13.8 - 16.7%. The higher the orange voltage, the lower the Brix value contained in oranges. Brix value 13.8 - 15.6% states the sweet level of orange fruit is sour, while the Brix value 16.7% states the sweet level of orange fruit is sweet. The results of testing the tool obtained an average error value of 0,004% and a tool accuracy value of 99,6%.